Bai'i as-Salam and Al-Istishna' in the Practice of Buying and Selling Orders from the Perspective of Fiqh Muamalah - Rizki Suandi; Lina Pusvisasari; Rahadian Taqi Yusup (Al-Abqori: Journal of Islamic Thought Studies, 2026)
Ba’i as-salam and al-istishna’ are Islamic sale contracts that allow transactions with advance payment and deferred delivery of goods. These contracts serve as solutions to the economic needs of society, particularly in the agricultural, trade, and manufacturing sectors. This article aims to examine the definitions of ba’i as-salam and al-istishna’, their Sharia foundations, the pillars and conditions of ba’i as-salam, the concept of parallel salam and istishna’, and examples of their application in modern economic life. This study employs a library research method using a descriptive-analytical approach. The findings indicate that ba’i as-salam and al-istishna’ are permissible in Islam as long as they comply with Sharia provisions, such as clarity of the contract object, agreed payment mechanisms, and avoidance of elements of gharar and riba.